8x+11=7-4x

Simple and best practice solution for 8x+11=7-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8x+11=7-4x equation:


Simplifying
8x + 11 = 7 + -4x

Reorder the terms:
11 + 8x = 7 + -4x

Solving
11 + 8x = 7 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
11 + 8x + 4x = 7 + -4x + 4x

Combine like terms: 8x + 4x = 12x
11 + 12x = 7 + -4x + 4x

Combine like terms: -4x + 4x = 0
11 + 12x = 7 + 0
11 + 12x = 7

Add '-11' to each side of the equation.
11 + -11 + 12x = 7 + -11

Combine like terms: 11 + -11 = 0
0 + 12x = 7 + -11
12x = 7 + -11

Combine like terms: 7 + -11 = -4
12x = -4

Divide each side by '12'.
x = -0.3333333333

Simplifying
x = -0.3333333333

See similar equations:

| =0.75 | | 900=0.75 | | e=0.75 | | ln(x-1)+ln(x-2)=ln(x+2) | | x+(x+3)=3x-5 | | 3690*x=1539554 | | -2(-9-p)=9 | | (x+1)(x+2)(x+3)=5 | | 3c-35=3 | | 12-f=9 | | X+z=9 | | -4b+b+-4=3 | | 3y+z=8 | | (x-8)/3=3 | | (x-8)/3 | | z=x+5y | | -10+8x=11+x | | 5(3x-12)=7x-12 | | 5x-4/2x-3=10(3-x)/17-4x | | x^2=1/x^2 | | 2x-3/7=3x/7-2x | | X*3=200 | | log(x+2)-logx=2 | | 8y+2=y-12 | | -5/8(16w-25)=35 | | 6x^2=5x-4 | | 3=12-15x | | 9x+2y=90 | | -307=6b+-7(-5b+-3) | | t^2-9t+18= | | -(1+8p)-6p=-3p-23 | | (5/6)x=5 |

Equations solver categories